2008
DOI: 10.1165/rcmb.2007-0132oc
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Turnover Kinetics in the Lungs of Mice Infected with Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae is the most prevalent cause of community-acquired pneumonia and is known to induce apoptosis and necrosis in macrophages in vivo. We analyzed the kinetics of alveolar and lung parenchymal macrophage replacement by newly recruited exudate macrophages in vehicle-treated and S. pneumoniae-challenged bone marrow chimeric CD45.1 mice. After lethal irradiation, CD45.1 alloantigen-expressing recipient mice were transplanted with bone marrow cells from CD45.2 alloantigen-expressing donor mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
69
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 21 publications
11
69
1
Order By: Relevance
“…45 Our gating strategy distinguishes ExMs from AMs, which are both CD11c ϩ AF ϩ on the basis of CD11b expression (present on ExMs and absent on AMs), as recently described. [33][34][35][36] In those studies, ExMs were specifically identified in the lungs of mice with bacterial or viral pneumonia, in which the numbers were much smaller than in the current study. The impressive quantity of ExMs that we identify in this model likely reflects the substantial inflammation induced by cryptococcal lung infection, with recruitment of up to 100 million CD45 ϩ leukocytes per mouse and critical reliance on lung macrophages for clearance of this organism.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…45 Our gating strategy distinguishes ExMs from AMs, which are both CD11c ϩ AF ϩ on the basis of CD11b expression (present on ExMs and absent on AMs), as recently described. [33][34][35][36] In those studies, ExMs were specifically identified in the lungs of mice with bacterial or viral pneumonia, in which the numbers were much smaller than in the current study. The impressive quantity of ExMs that we identify in this model likely reflects the substantial inflammation induced by cryptococcal lung infection, with recruitment of up to 100 million CD45 ϩ leukocytes per mouse and critical reliance on lung macrophages for clearance of this organism.…”
Section: Discussioncontrasting
confidence: 59%
“…[33][34][35][36] Expression of CD11b, along with varying reports of increased major histocompatibility complex (MHC) class II and costimulatory molecules, distinguishes ExMs from AMs. 33 Exudate macrophages express iNOS indicative of effector function.…”
mentioning
confidence: 99%
“…Briefly, mice were euthanized with an overdose of isoflurane (Baxter, Unterschleissheim, Germany) and bronchoalveolar lavage was performed by repeated intratracheal instillation of 300 μl aliquots of cold PBS supplemented with EDTA (Versen; Biochrom, Berlin, Germany) into the lungs and careful aspiration, until a BAL volume of 1.5 ml was collected as describedrecently (27)(28)(31)(32). Subsequently, BAL was continued until an additional volume of 4.5 ml was collected.…”
Section: Determination Of Bacterial Loads In Bronchoalveolar Lavage Fmentioning
confidence: 99%
“…Collection of BAL for the isolation of resident alveolar macrophages and alveolar recruited leukocytes from mice of the various treatment groups was done as described in detail recently (27)(28)(31)(32). Quantification of BAL fluid neutrophils, eosinophils, and lymphocytes was done on differential cell counts of Pappenheim-stained cytocentrifuge preparations, using overall morphological criteria, including cell size and shape of nuclei and subsequent multiplication of those values by the respective absolute BAL cell counts (27)(28)(31)(32).…”
Section: Bal and Preparation Of Lung Parenchymal Tissuementioning
confidence: 99%
See 1 more Smart Citation